Average Error: 0.0 → 0.0
Time: 10.6s
Precision: 64
$begin + \left(end - begin\right) \cdot t$
$begin + \left(end - begin\right) \cdot t$
begin + \left(end - begin\right) \cdot t
begin + \left(end - begin\right) \cdot t
double f(double begin, double end, double t) {
double r1847800 = begin;
double r1847801 = end;
double r1847802 = r1847801 - r1847800;
double r1847803 = t;
double r1847804 = r1847802 * r1847803;
double r1847805 = r1847800 + r1847804;
return r1847805;
}


double f(double begin, double end, double t) {
double r1847806 = begin;
double r1847807 = end;
double r1847808 = r1847807 - r1847806;
double r1847809 = t;
double r1847810 = r1847808 * r1847809;
double r1847811 = r1847806 + r1847810;
return r1847811;
}



Try it out

Results

 In Out
Enter valid numbers for all inputs

Derivation

1. Initial program 0.0

$begin + \left(end - begin\right) \cdot t$
2. Final simplification0.0

$\leadsto begin + \left(end - begin\right) \cdot t$

Reproduce

herbie shell --seed 1
(FPCore (begin end t)
:name "begin + (end - begin) * t"
:precision binary64
(+ begin (* (- end begin) t)))